LABORATORY DIAGNOSIS OF THALASSEMIA - Isakulova Muhabbat Mardanovna; Ibragimova Nadiya Sabirovna; Anvarhonova Muhtasarhon Asrorhon kizi (TADQIQOTLAR.UZ, 2024)
Annotation. Laboratory diagnosis of thalassemia occupies an important place in  the  modern  approach  to  the  treatment  and  prevention  of  this  hereditary  disease. Thalassemia, a group of disorders involving hemoglobin synthesis, can cause serious complications  including  anemia,  cardiovascular  problems  and  growth  retardation. Early diagnosis is critical to selecting optimal treatment methods and monitoring the patient's condition.